Cognitive-interpretive strategies in the development of critical thinking in graduate students at a public university in Lima - Arbieto Cortez, Cecilia (2025)
The objective of this research was to develop a pedagogical proposal to foster critical thinking in third-cycle master’s students specializing in University Teaching at a public university in Lima. This study emerged from the need to promote activities that strengthen competencies associated with this type of thinking among students. The methodology was framed within the socio-critical paradigm, with a projective approach and holistic design, as the changes sought to encourage reflection and action among the 108 participants, selected through probabilistic sampling. During the diagnostic phase, a survey validated by experts was applied, consisting of 42 items distributed across 10 dimensions, aimed at assessing competencies related to critical thinking. The results revealed that students possess some competencies that support critical thinking, such as skills for critical reading and content interpretation. Despite these strengths, areas for improvement and opportunities to enhance participants’ cognitive skills were identified. It was concluded that designing an intervention strategy, such as the proposed one, can enhance existing competencies and develop new ones, promoting autonomy, critical thinking, and reflection on the information and knowledge they access.